Rabindranath Tagore and the Foundations of Indian English Literature: A Literary and Philosophical Contribution (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Rabindranath Tagore, the first non-European Nobel Laureate in Literature, holds a seminal place in the history of Indian writing in English. Though he predominantly wrote in Bengali, his English translations—particularly Gitanjali—garnered international acclaim and positioned Indian literature on the global map. This article explores Tagore's contribution to Indian English literature not just as a translator of his own works, but as a philosophical voice that redefined Indian aesthetics, spiritualism, and humanism for the English-speaking world. Tagore's writings embody a rare synthesis of tradition and modernity, East and West, nationalism and universalism. Through an analysis of his literary philosophy, translations, and critical reception, this paper evaluates how Tagore laid the groundwork for future generations of Indian writers in English and contributed to the development of a distinct Indian voice in global literature.